(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The better knowledge of the Iberian language gained by scholars in recent times may allow us to formulate the hypothesis of reading Sic as the Iberian name of a river instead of Latin sic ‘so – this way’ in a passage of Ora Maritima, by the Roman author Avienus.